2020
DOI: 10.1111/tid.13276
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus and human metapneumovirus after allogeneic hematopoietic stem cell transplantation: Impact of the immunodeficiency scoring index, viral load, and ribavirin treatment on the outcomes

Abstract: Introduction Respiratory viral infections are a major cause of morbidity and mortality among stem cell transplant recipients. While there is a substantial amount of information on prognostic factors and response to ribavirin therapy is available for RSV infections, this information is largely lacking for hMPV. Patients and methods In total, 71 patients were included in this study: 47 patients with RSV and 24 with hMPV. Forty‐one patients presented as an upper respiratory tract infection (URTI) and 30 as a prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
0
5
0
2
Order By: Relevance
“…The influence of coinfections on severe viral respiratory disease is still unclear; however, RSV‐MPV coinfections in immunocompetent patients are generally comparable to single‐virus infections with regard to oxygen supplementation, ICU admission, or the need for mechanical ventilation 13‐15 . Immunodeficiency in pediatric or adult HSCT recipients is a factor contributing to disease severity, and overall mortality in patients with post‐transplant RVI is reportedly 10% 16‐18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of coinfections on severe viral respiratory disease is still unclear; however, RSV‐MPV coinfections in immunocompetent patients are generally comparable to single‐virus infections with regard to oxygen supplementation, ICU admission, or the need for mechanical ventilation 13‐15 . Immunodeficiency in pediatric or adult HSCT recipients is a factor contributing to disease severity, and overall mortality in patients with post‐transplant RVI is reportedly 10% 16‐18 …”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Immunodeficiency in pediatric or adult HSCT recipients is a factor contributing to disease severity, and overall mortality in patients with post-transplant RVI is reportedly 10%. [16][17][18] Due to a lack of proven therapies, initial COVID-19 treatment was based on the recommendations issued in April 2020. Moreover, despite the large number of clinical trials started, no results of well-designed prospective RCTs that support chloroquine/hydroxychloroquine or azithromycin efficacy in SARS-CoV-2 infection are available as of the date of publication.…”
Section: A S E Rep Ortmentioning
confidence: 99%
“…Recent two studies indicated that the rates of progression to LRTI with HMPV were approximately 30% and the risk was not significantly different from that with RSV [7 ▪▪ ,48]. The high-risk ISI group was associated with a higher risk of progression and mortality.…”
Section: Risk Factors For Severity In Human Metapneumovirusmentioning
confidence: 96%
“…Monoclonal antibodies (mAb) such as palivizumab and nirsevimab have been proven to be quite effective in preventing severe cases of RSV, particularly when dealing with RSV-related LRTI [23,[56][57][58][59][60], but again no specific recommendations for BMT recipients have been issued. To date, the only available treatment option is represented by ribavirin [45,[61][62][63][64][65][66][67][68][69][70]; however, it should be stressed that neither the United States Food and Drug Administration (FDA) nor the European Medicine Agency (EMA) has approved the use of ribavirin for conditions other than hepatitis C [18,44,61,67,69].…”
Section: Introductionmentioning
confidence: 99%